Advances in Intelligent Data Analysis and Its Applications, 2nd Edition (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue highlights the growing importance of intelligent data analysis and its profound applications in addressing the challenges of the big data era. As a key driver of innovation and progress across diverse sectors, intelligent data analysis requires robust research and implementation to derive actionable insights from vast, complex datasets. By fostering advancements in various industries, this field plays a vital role in meeting the dynamic demands of modern data-centric environments. The aim of this Special Issue is to delve into cutting-edge developments in intelligent data analysis and their applications. Topics span a broad spectrum, including advanced data mining algorithms, machine learning integration, natural language processing innovations, granular computing frameworks, cognitive computing techniques, and hybrid approaches. This initiative seeks to provide insights into the academic growth of the field while enabling research and industry to adopt transformative solutions that shape its future trajectory. Scholarly and professional contributions have enriched intelligent data analysis, covering domains such as machine learning, data mining, social network analysis, machine vision, and hybrid computational paradigms. Building on the inaugural volume's success, this Special Issue consolidates recent developments with a focus on real-world applications, encompassing sectors like finance, healthcare, business intelligence, engineering, and environmental science.